المصطلح النحوي وتعليمية اللغة العربية - كرام, قمرة; تامة, الزهرة; بكاري, هدى (University of Eloued جامعة الوادي, 2024)
- اهتمّ بحثنا هذا بدراسة المصطلح النّحوي وتعليميّة اللّغة العربية في الطّور المتوسّط، فجاءت خطّة البحث في فصلين: الفصل الأوّل تناولنا فيه مفهوم المصطلح النّحوي وتطرّقنا إلى تعليميّة اللّغة العربيّة، وواقعها في الطّور المتوسّط، وفي الفصل الثّاني بدأنا بتقديم المدارس النّحويّة ومجهوداتها العظيمة في وضع علم النّحو، وقد كان للبصرة الفضل الكبير في ذلك، فاتّسم هذا العلم بالصّعوبة وتعدّد مصطلحاته في بدايتة، ولحاجة النّاشئة لتعلّمه، سعى النّحاة قديما وحديثا لتيسيره وجعله علما وظيفيّا تعليميّا، فعلم النّحو ومصطلحاته ليس غاية بل هو وسيلة للتّعليم . - Our research focused on studying the grammatical term and Arabic language education in the middle school level. The research plan consisted of two chapters: in the first chapter, we discussed the concept of grammatical terminology and addressed Arabic language education and its reality in the middle school level. In the second chapter, we began by presenting grammatical schools and their great efforts in establishing the science of grammar, with Basra playing a significant role in this regard. This science was characterized by its difficulty and the multiplicity of its terms in its beginning, and due to the need for learners to study it, grammarians, both ancient and modern, sought to simplify it and make it a functional educational science. Therefore, the science of grammar and its terminology is not an end in itself but rather a means of education..
دراسة وصفية تحليلية في الطور المتوسط كتاب السنة الرابعة أنموذجا
415/04
Keywords: المصطلح النحوي – التعليمية-الطور المتوسط -اللغة العربية; Grammatical term - educational - intermediate stage - Arabic language